Analysis of the impact of the Covid-19 epidemic through the sojourn tax and the attitudes of the respondents - Jakovljević Nemanja (Trendovi u Poslovanju)
The impact of the global epidemic caused by the appearance and spread of the Covid19 virus has led to strong effects on all human labor activities, of which tourism stands out, as the activity most affected by the virus. Less than two years have passed since the outbreak of the epidemic, and tourism, as an activity, has slowly begun to return to its pre-epidemic state since the complete collapse at the interstate level. This paper will analyze the impact of the current global epidemic on tourism in the Republic of Serbia through the analysis of the sojourn tax in the period of 3 consecutive years from 2018 to 2020, while researching the attitudes of sampled respondents on tourist visits during the epidemic. The issue of the tourist tax and its positive and negative sides will also be considered. The main conclusion is that the revenues from the tourist tax in most local self-government units recorded a declining trend, which in most cases was not significant, as a result of a good state strategy and encouragement of domestic tourism during the global closure and crisis caused by the pandemic Covid19. Most of the total number of respondents are satisfied with the level of tourist services in their home country and after the pandemic they will visit domestic tourist destinations more often.